The Effect of Graphene on the Deposition and Mechanical Property of Ni-Fe-Graphene Composite Coating. Issue 5 (7th April 2018) - Li, Na; Zhang, Lan; Zhu, Yongchao; Xu, Miting; Xu, Yuxi; Ruan, Xinwei; Ma, Huizhong
Abstract : Electrodeposited Ni-Fe-Graphene composite coatings have been prepared on the aluminum alloy substrate from alkaline Ni-Fe alloy electrolyte with varied graphene nanoplatelets (GNPs) concentrations from 0.05 g L −1 to 3 g L −1 . The effect of graphene concentration on the microstructure, element composition and mechanical property of Ni-Fe-Graphene composite coating has been investigated. The results indicate that the incorporation of GNPs into the coatings promotes the co-deposition of Ni 2+ in the electrolyte. Graphene content presents a negative correlation with the iron content in the composites. Graphene content and dispersion in the coatings both play a key role in the properties and when graphene concentration is 1 g L −1, Ni-Fe-Graphene composite coating exhibits the highest hardness (912.6 HV) and best wear resistance (friction coefficient of 0.1990). It is attributed to the grain refinement, excellent mechanical property and self-lubricant of GNPs. The morphology, microstructure and element composition of deposited composites have been characterized using scanning electron microscopy (SEM), energy disperse spectroscopy (EDS), X-ray diffraction (XRD). Raman spectrum is used to characterize the presence of GNPs in the composites.